Incidence, Risk Factors, and Clinical Outcomes of Post-Renal Transplant Erythrocytosis: A Study of 126 Kidney Transplant Recipients - Muhammad Tassaduq Khan, Rashid Bin Hamid, Zulfiqar Ahmed, Sana Abid, Uzma Ibrahim, Hafiz Furqan Ahmed, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Post-renal transplant erythrocytosis (PTE) is a rare but recognized complication following kidney transplantation. It is characterized by elevated red blood cell mass, often due to increased erythropoietin (EPO) production from the transplanted kidney. This study aims to investigate the incidence, risk factors, and clinical outcomes associated with PTE in kidney transplant recipients. Methods: A retrospective cohort study was conducted on 126 kidney transplant recipients at a Dow University Hospital , Karachi during from the period April 2022 and September 2023. Data on demographic characteristics, pre-transplant renal function, graft function, immunosuppressive regimens, and hemoglobin levels were collected. Patients were categorized based on the presence or absence of erythrocytosis. Results: Of the 126 patients, 18 (14.3%) developed post-transplant erythrocytosis. The mean hemoglobin level in the erythrocytosis group was significantly higher than in the non-erythrocytosis group (17.5 g/dL vs. 14.3 g/dL, p < 0.01). Significant predictors of PTE included higher baseline erythropoietin levels, hyperfunctioning graft, and immunosuppressive use, particularly corticosteroids. Conclusion: Post-renal transplant erythrocytosis occurs in a notable proportion of kidney transplant recipients. It is most commonly associated with improved graft function, increased EPO production, and corticosteroid use. Close monitoring of hemoglobin levels in these patients is essential to prevent complications such as thromboembolism and hyperviscosity. Keywords: Post-renal transplant erythrocytosis, kidney transplantation, erythropoietin, immunosuppression, hemoglobin, graft function, corticosteroids.